Metabolite-Specific Echo-Planar Imaging of Hyperpolarized [1-13C]Pyruvate at 4.7 T - Tyler Blazey; Galen D Reed; Joel R Garbow; Cornelius von Morze (Tomography, 2021)
Although hyperpolarization (HP) greatly increases the sensitivity of 13C MR, the usefulness of HP in vivo is limited by the short lifetime of HP agents. To address this limitation, we developed an echo-planar (EPI) sequence with spectral-spatial radiofrequency (SSRF) pulses for fast and efficient metabolite-specific imaging of HP [1-13C]pyruvate and [1-13C]lactate at 4.7 T. The spatial and spectral selectivity of each SSRF pulse was verified using simulations and phantom testing. EPI and CSI imaging of the rat abdomen were compared in the same rat after injecting HP [1-13C]pyruvate. A procedure was also developed to automatically set the SSRF excitation pulse frequencies based on real-time scanner feedback. The most significant results of this study are the demonstration that a greater spatial and temporal resolution is attainable by metabolite-specific EPI as compared with CSI, and the enhanced lifetime of the HP signal in EPI, which is attributable to the independent flip angle control between metabolites. Real-time center frequency adjustment was also highly effective for minimizing off-resonance effects. To the best of our knowledge, this is the first demonstration of metabolite-specific HP 13C EPI at 4.7 T. In conclusion, metabolite-specific EPI using SSRF pulses is an effective way to image HP [1-13C]pyruvate and [1-13C]lactate at 4.7 T.